KONSTRUKSI REALITAS MEDIA DAN KEKUASAAN Studi Program Infotainmen Selebritis dalam Pemberitaan Pornografi di TV - , SUKARNO M. ADAM, S.Sos; , Prof. Dr. Heru Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Power in social reality, not only spins on a rigid structural circuit in political institutions. However, the power is everywhere as proposed by Michel Foucault. This study stressed that contemporary power uses new tactics and âpowerfulâ through media as its instrument both print and electronic, particularly this paper emphasizes on television. Television uses text and discourse in constructing and perpetuating âpowerâ. One of the blossoming site of a discourse instrument is an infotainment program on television, which is shown in its discourse on pornography involved Ariel and Luna Maya. This study uses the CDA methods (Critical Discourse Analysis) proposed by Norman Fairclough, which in this analysis the data obtained from the text in the infotainment and in-depth interview with media managers and audience. The theory used is Michel Foucaultâs discourse and Antonio Gramsciâs hegemony. Discourse is seen as a âweaponâ of conquest and hegemony is seen as a method of conquering the people (audience). Text or discourse in the infotainment program, which aired through television is part of the discourse that shocked the people in 2010. Ariel Peterpan and Luna Maya, two of the top and most popular artists at the time, were fragile to be made news in infotainment programs. At the very period, three consecutive days (6-8 June 2010) the infotainment rating rose up 25 percent. This means that with the news that display pornography in the infotainment, the program not only presents information or knowledge, let alone education. However, infotainment became the entertainment program that puts sensational news to attract audience to win the market. Two of infotainment programs, Silet and I Gosip Pagi, and the above pornography discourse, was an entrance as well as representation to track and understanding what is actually constructed in infotainment. In accordance with a critical discourse analysis, text is the first instrument for understanding the phenomenon. Then proceed with the discourse practice and socio-cultural practices. This research finds some important things. Starting from the result of the first analysis, text, it was found that the text in the narrative (scripwriter) infotainment was full of sensational words and language, metaphors and exaggeration of the news. Second, discourse practice, the manager of infotainment (producer/reporter) explained that the infotainment put more priority on attractive news for pursuing profit. Third, socio-cultural practice, it was found that infotainment more as an program is entertaining. This means the infotainment have been able to construct a false consciousness in the life of the people wrapped with entertainment containing any kind of life-style. Of the three steps, it can be understood that the infotainment was mainly designed for profit, market, and interests of politicaleconomic of media which was very capitalistic.